The condition and changes assessment of general socio-economic development of Ukraine between 1992 and 2012 on the basis of spacecraft survey materials DMSP/OLS (USA) about the night lightening of the territory - Lyalko, V.I.; Elistratova, L.A.; Apostolov, A.A.; Khodorovsky, A.Ya. (Reports of the National Academy of Sciences of Ukraine, 2018)
We performed the correlation assessment of the changes for main socio-economical factors of Ukraine with the analysis of intensity of night lightening within spacecraft survey DMSP/OLS data. The archive of satellite imagery and statistical data on the urban and rural population numbers and on the gross regional product between 1992 and 2012 were used. We established that satellite data on the night lightening of the territory form the DMSP/OLI satellite are correlating with indicators that characterize the socio-economical condition of the country, and can be used in case of independent remote monitoring of the socio-economical development of Ukraine.